An investigation into how the timing of nutritional supplements affects the recovery from post-exercise fatigue: a systematic review and meta-analysis - Cheng, Guangxin; Zhang, Zhongchen; Shi, Zhiming; Qiu, Yepeng (Frontiers in Nutrition, 2025)
BackgroundThis study used a systematic evaluation and meta-analysis to determine how the timing of nutritional supplements affected the recovery from post-exercise weariness. A vital component of enhancing athletic performance and advancing health is post-exercise recovery, where nutritional supplements are crucial. Although it has been demonstrated that supplementing timing may affect recovery outcomes, there is conflicting evidence about the best time to take supplements.MethodsWe thoroughly searched several academic databases and screened for inclusion of randomized controlled trials, clinical trials, and observational studies that satisfied the criteria in order to examine the effects of varying nutritional supplementation timing (immediate vs. delayed supplementation) on fatigue recovery.ResultsThe findings demonstrated that, in comparison to delayed supplementation, protein and carbohydrate supplementation right after exercise dramatically expedited muscle recovery, glycogen recovery, and decreased tiredness. Furthermore, the impact of supplementation timing on recovery effects differed depending on the individual and the type of exercise (e.g., strength training, endurance exercise, and high-intensity interval training).ConclusionRecovery from post-exercise weariness is significantly impacted by the timing of nutritional intake. Supplementing with protein and carbohydrates right after exercise, particularly after intense exercise, can help with tiredness relief, muscle recovery, and glycogen replenishment.